Mucosal Thickening Occurs in Contralateral Paranasal Sinuses following Sinonasal Malignancy Treatment - Maxfield, Alice Z.; Chambers, Kyle J.; Sedaghat, Ahmad R.; Lin, Derrick T.; Gray, Stacey T. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objective To investigate the incidence and degree of contralateral sinus disease following treatment of sinonasal malignancy (SNM) using radiological findings as an outcome measure.Study Design Retrospective case series.Setting Tertiary referral academic center.Participants Patients with SNM treated with surgical and adjuvant radiotherapy with or without concurrent chemotherapy.Main Outcome Measures Pre- and posttreatment computed tomography and magnetic resonance imaging scans, Lund–Mackay (LM) score, date of diagnosis, chemotherapy, and dosage of radiation therapy (RT).Results There was a significant difference between pre- and posttreatment LM scores (p < 0.001) of the contralateral paranasal sinuses. There was no statistical significance between the change in pre- and posttreatment LM scores and patient age, gender, chemotherapy, RT dosage, and time lapse between diagnosis and when we performed this study in the univariate and the multivariable analyses.Conclusions Following treatment of SNM with surgical resection and RT, there was a significant increase in incidence and degree of mucosal thickening of the contralateral sinus by LM grading that persisted after the completion of treatment. This indicates the need for long-term follow-up to monitor for chronic rhinosinusitis as a delayed complication following treatment of SNM.
Keywords: sinonasal malignancy; mucosal thickening; Lund–Mackay